Pengembangan Media Pembelajaran IPS Pada Buku Tema 1 ASEAN Untuk Siswa Kelas VI SD - Amala Sundari; Fany Isti Fauzia; Tin Rustini (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2023)
Social Sciences is a subject studied by students since the elementary school level which of course requires learning media as an aid in the teaching and learning process. The background of this research is the limited use of learning media in social studies subjects causes students to experience boredom because the learning process is less fun. Social studies learning is still dominated by teachers which results in a lack of interaction between students when participating in the learning process. The purpose of the research is to develop learning media that will be applied to learning as social studies learning media for ASEAN countries in grade VI SD. In this study, using the type or approach of library research with library data collection methods, reading and recording and processing research materials from journals, books, articles, magazines, websites with various types of publications that are relevant to the development of learning media for ASEAN Class. VI SD. The results of the study show that the learning media Smart Sticker Spin Wheel on the material of ASEAN countries in social studies learning is very suitable to be used in the social studies learning process in class VI SD.